Implementasi Metode Trend Moment Untuk Prediksi Penjualan Barang - Jarot Dian Susatyono; Febryantahanuji Febryantahanuji; Haryo Kusumo; Sindhu Rakasiwi (STEKOM PRESS, 2024)
Problems that still occur in the current condition of PT MASSINDO, which is located at Jalan Gatot Subroto no 23, Block 9, Semarang City, in the process of selling springbeds, still often experience fluctuations in sales of several types and types of springbeds which are influenced by the number of goods to be sold which do not match the number of sales, thus causing a lot of losses. Therefore, it is necessary to carry out an analysis process on sales that will occur in the coming period to increase the company's sales turnover and make cash turnover more stable. The method that will be used as a consideration for companies to stabilize sales of goods is the Trend Moment method.